Emerging resistance genes in the aquatic ecosystems: a review / Wardina Afrina Khairil Rijal … [et al.] - Khairil Rijal, Wardina Afrina; Zulkifli, Siti Hazirah; Abdul Rahim, Farihah Aiman; Rosliza, Rosli; Che Zakaria, Nur Zafirah; Mohd Faiz, Adlynn; Sarizan, Nur Maisarah; Ahmad Kamil, Khairunnisa (Universiti Teknologi MARA, Sabah, 2023)
Antibiotic use may hasten the emergence of antibiotic resistance genes (ARGs) in bacteria, posing health concerns to humans and animals alike. The emergence of ARGs in aquatic ecosystems is becoming a growing problem around the world. Hundreds of different ARGs encoding antibiotic resistance have been discovered in bacteria found in sewage, effluent treatment facilities, surface water, groundwater, and even drinking water. Antibiotic resistance genes can be transmitted from one cell to another by conjugation, transformation, or transduction. This gene exchange allows resistance to spread quickly within a bacterial community and between various species of bacteria. This is more so in an ideal environment such as aquatic ecosystems. The purpose of this article is to review the presence of ARGs in various aquatic ecosystems and how this will affect humans. Based on 30 selected studies in the last five years (2017-2022), we notice that ARGs can be found in various aquatic ecosystems, including surface water, wastewater, and plastic and microplastic debris found in these ecosystems. There are some studies showing ARGs are directly affecting humans, but there are also many ongoing efforts and technologies to reduce ARGs in aquatic ecosystems. From the discussion, we conclude that antibiotic resistance genes can thrive in various aquatic ecosystems, which offer an ideal environment for their replication. Although aimed at reducing pollutants in the environment, wastewater treatment plants (WWTPs) have been identified as potential hubs for the spread of antibiotic resistance determinants into aquatic ecosystems, showing the importance of continuous monitoring and finding solutions.